Epidemiology of pediatric tracheotomy: A population-based study using National Health Insurance Research Database in Taiwan. (January 2022) - Kang, Kun-Tai; Lin, Yu-Sheng; Lin, Che-Yi; Lee, Chia-Hsuan; Hsu, Wei-Chung
Abstract: Objective: Tracheostomy in children is a surgical procedure with considerable morbidity and mortality. However, there is still a lack of population-based survey in pediatric tracheostomy. This study analyses population-based data in pediatric tracheostomy among different ages in Taiwan. Methods: This study used National Health Insurance Research Database in Taiwan. All children (aged <18 years) who underwent tracheostomy during 1997–2016 were identified. We retrieved data regarding baseline characteristics, perioperative care, and mortality associated with pediatric tracheostomy, and compared differences in variables between different age groups. Results: We observed that 2300 children received tracheostomy (mean age, 8.7 years; 64% boys). Regarding the age group distribution of the patients, 585 (25.4%) were infants (<1 year), 227 (9.9%) were toddlers (1–3 years), 175 (7.6%) were preschool-aged children (3–6 years), 317 (13.8%) were school-aged children (6–12 years), and 996 (43.3%) were adolescents (12–18 years). Surgical indications included pulmonary disorders (64.9%), neurological disorders (38.4%), trauma (32.3%), head injury (25.2%), and congenital anomalies (21.5%). Of these patients, 94.9% required intensive care unit (ICU) care, with the mean length of ICU stay being 63.8 days. The mean length of hospital stay was 74.5 days. The overall mortality at the last follow-up was 43.96% (1011/2300), and the tracheostomy related mortality at the last follow-up was 1.43% (33/2300). Compared with adolescents, infants more commonly underwent tracheostomy in the northern area (66.7% vs 37.2%, P < .001), more commonly received tracheostomy indicated by congenital anomalies (53.7 vs 4.6%, P < .001), had longer ICU stays, had longer hospital stays (100.7 vs 57.5 days, P < .001), and had a higher 5-year mortality rate (42.4 vs 29.6%, P < .001). Multivariable logistic and Cox regression models revealed that young age was associated with an increased risk of prolonged hospital stay and long-term mortality, respectively. Conclusions: This study elaborates the epidemiology of pediatric tracheostomy in different age groups.